Rediscovered Cranial Material of Venaticosuchus rusconii Enables the First Jaw Biomechanics in Ornithosuchidae (Archosauria: Pseudosuchia) - Von Baczko, Belen (2018)
During the Triassic period, pseudosuchians presented a broader variety of feeding habits than those seen nowadays, including herbivorous and omnivorous as well as carnivorous diets. Based on their general anatomy, ornithosuchids have been historically proposed to be either hunters or scavengers. The rediscovered cranial materials of the ornithosuchid Venaticosuchus herein described in detail enabled the reconstruction of its jaw musculature and a geometric biomechanical analysis to study the possible feeding habits of ornithosuchids. The muscles were reconstructed based on inferences of their osteological correlates seen in their closest living relatives, such as Caiman, Alligator, and Iguana. Consequently, the jaws were considered a third-class lever system and the moment arms were calculated for the adductor and depressor musculature. The study of the three species of ornithosuchids (Ornithosuchus, Venaticosuchus and Riojasuchus) revealed greater similarities between ornithosuchids and aetosaurs, in spite of their different feeding habits, than between ornithosuchids and crocodylians. The relative bite force of Venaticosuchus resulted higher than that of other ornithosuchids, aetosaurs and Alligator. The elevated bite force identified for ornithosuchids together with their low bite speed and the morphology of their constricted snouts, suggest features more compatible with scavenging feeding habits. Ornithosuchids were not the apex predators of the Late Triassic continental communities but were more likely regarded to have scavenged or preyed on small animals such as procolophonids, sphenodontians, juvenile aetosaurs, erpetosuchids, cinodonts, and dicynodonts that did not exceed them in size.